Fortalecimiento De Las Capacidades Gerenciales En Finanzas Y Tributarias En Los Comerciantes Del Sector Automotriz Del Barrio Eduardo Santos (2022)
The objective of this research was to design strategies for the strengthening of managerial capacities in finance and taxes in the merchants of the automotive sector of the Eduardo Santos neighborhood, for its development a mixed methodology of quantitative and qualitative, descriptive and participatory action approach was implemented in where the survey was used as an instrument and a sample of 52 participants was taken. The results showed that 100% of the respondents are natural persons, where 78.8% do not know their duties as merchants, 90.4% do not know what the financial statements are, 96.2% do not have accounting knowledge or tax and 96.2% are interested in training on these issues. A training plan was applied in which topics such as basic concepts of finance, accounting aspects and tax aspects were developed, the training was virtual and the perception index showed that 80% of the participants felt satisfied with the topics addressed. . Likewise, a didactic booklet was elaborated in a simple and straightforward way to serve as a help tool for merchants. It was concluded that training the merchants of the Eduardo Santos neighborhood allowed them to acquire basic knowledge in financial and tax aspects, which contributes to improving their tax culture, compliance with their obligations and better control and management of their businesses.